Internet use and self-rated health among Chinese older adults: the role of social engagement and social support - Li, Pei-Qi; Sun, Guo-Yuan; Zhao, Xue-Xue; Hu, Zheng-Xin; Gan, Kai-Peng (Frontiers in Public Health, 2025)
This study examines how social engagement and social support affect association between internet use and older adults' self-rated health in Kunming. An analysis of 518 community-dwelling older adults reveals that internet use significantly enhances their self-rated health. Social engagement mediates this relationship, while social support strengthens the beneficial impact of social engagement on self-rated health. Additionally, social support amplifies the mediating role of social engagement, suggesting that greater social support enhances the benefits of social engagement on health outcomes. Our findings emphasize the significance of fostering social engagement and providing robust social support to improve older adults' health.